2018
DOI: 10.18870/hlrc.v8i2.422
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Effectiveness of a Medical School Musculoskeletal Curriculum at an Academic Medical Center

Abstract: Background: Musculoskeletal disorders are common medical problems encountered by physicians and affected 126.6 million Americans in 2012.  Musculoskeletal education has inadequate in United States medical schools. Objective: To determine the musculoskeletal competency of third year medical students. Methods: A cross-sectional 25-question nationally validated musculoskeletal competency exam was given to the third year medical students.  A survey was given to second and third year medical students to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Furthermore, despite being the only assessment tools to populate the literature and undergo validation in musculoskeletal education, they both fail to assess musculoskeletal clinical skills, or psychometric factors, both core components of ultimate competency in the discipline. Moreover, the perceived confidence and attitude of medical students for musculoskeletal disease is concerningly low 28,30,33,34,36 . Despite variability in the tool assessing clinical confidence between studies, and marginal increments observed with advancing years of medical education, 28,30,33 no student reported above average confidence in musculoskeletal medicine in our analysis, regardless of stage of study 28,30,33,34,36 .…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Furthermore, despite being the only assessment tools to populate the literature and undergo validation in musculoskeletal education, they both fail to assess musculoskeletal clinical skills, or psychometric factors, both core components of ultimate competency in the discipline. Moreover, the perceived confidence and attitude of medical students for musculoskeletal disease is concerningly low 28,30,33,34,36 . Despite variability in the tool assessing clinical confidence between studies, and marginal increments observed with advancing years of medical education, 28,30,33 no student reported above average confidence in musculoskeletal medicine in our analysis, regardless of stage of study 28,30,33,34,36 .…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, the perceived confidence and attitude of medical students for musculoskeletal disease is concerningly low 28,30,33,34,36 . Despite variability in the tool assessing clinical confidence between studies, and marginal increments observed with advancing years of medical education, 28,30,33 no student reported above average confidence in musculoskeletal medicine in our analysis, regardless of stage of study 28,30,33,34,36 . Furthermore, student‐reported adequacy of their musculoskeletal education was consistently suboptimal 37,38 …”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations